Unexpected uses for obsidian: experimental replication and use-wear/residue analyses of chopping tools. (February 2015) - Kononenko, Nina; Torrence, Robin; White, Peter
Abstract: Large flaked stemmed artefacts with a morphological resemblance to axes or adzes have been recovered from stone quarries in West New Britain, Papua New Guinea, but they are made from obsidian, a volcanic glass generally considered too brittle for tasks demanding tough, long-lasting edges, such as chopping wood. To evaluate the potential of obsidian for percussive woodworking, 11 replica obsidian tools were used as axes and adzes. Although breakage was common and the tools suffered extensive edge damage, they were surprisingly effective as chopping tools. The patterns of use-wear and residue traces on the experimental tools informed the analysis of 27 archaeological artefacts which were found to have been used as axes or adzes with the addition of sawing in a few cases. As these tools have not been found outside the quarries, their occurrence suggests that during this period some forms of woodworking took place only where there was an abundant supply of raw material. The limited spatial distribution of obsidian chopping tools raises questions about the nature of forest clearance and woodworking in this tropical environment. Highlights: Obsidian axes and adzes in New Britain only occur c. 6000–3200 BP. Experiments show brittle obsidian makes effective heavy percussion tools. Self-sharpening prolongs the use-life of obsidian wood-chopping tools. 27 archaeological tools were identified as adzes and axes. Finding them only at quarries implies specialized uses for obsidian chopping tools.